Empowering Narratives: Critical Discourse Analysis of Gender Resistance in “Enola Holmes” Movie - Kadek Devi Kalfika Anggria Wardani; Made Devi Ranita Ningtara; Anak Agung Ngurah Eddy Supriyadinata Gorda (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
This research examines gender resistance in the film Enola Holmes through Sara Mills' critical discourse approach. The study focuses on how the film's narrative challenges gender stereotypes by portraying a strong, independent female lead in an adventure story that defies typical gender expectations in popular media. Using a qualitative descriptive method, the study applies Mills' framework to analyze language and narrative elements that shape Enola’s character. Concepts like subject positioning, objectification, and audience reception are explored to demonstrate how Enola challenges traditional gender roles. The analysis reveals implicit critiques of gender inequality, especially in political and social contexts within the film’s narrative. Enola’s portrayal as an active agent of change, intelligence, and empowerment is central, encouraging viewers to reconsider traditional gender roles and advocate for equality. Her journey of self-understanding prompts viewers to reevaluate their own perceptions of gender roles. These findings highlight the film’s role in promoting gender equality and social change, offering insights into how such narratives can influence societal perceptions. This study expands discussions on gender representation in media, emphasizing the significance of empowering female characters in reshaping cultural conversations around gender roles and empowerment.